STUDY OF VARIABLES AFFECTING DIVIDEND POLICY IN MANUFACTURING COMPANIES ON THE INDONESIA STOCK EXCHANGE - Akhiruddin, Anita (Journal Universitas Muhammadiyah Gresik Engineering, Social Science, and Health International Conference (UMGESHIC), 2021)
Free cash flow (FCF), debt, and company growth are important factors in determining dividend policy. Dividends are very meaningful for shareholders to increase their wealth, on the other hand, dividends are a source of funds that can be used for investments that produce high returns. In addition, dividends are a positive signal for investors, if the company regularly distributes dividends, this results in a high share price of the company. The manager needs to consider a dividend strategy that can benefit the company's continuation in the future as well as stockholder confidence.      The sample of this research consists of the manufacturing industry on the Indonesia Stock Exchange and starting from 2016-2019 with a total of 32 samples. This research aims to prove the factors of free cash flow (FCF), debt and dividends and their effect on dividend policy by using multiple regression models. The result of the research illustrates that there is a negative effect between free cash flow and dividend policy and this hypothesis is rejected because it is contrary to the hypothesis made. Meanwhile, dividend policy is influenced by debt policy and the result is significantly negative, and company growth has a negative and significant impact on debt policy. Keywords: Dividend, FCF, Debt, Growth     Free cash flow (FCF), debt, and company growth are important factors in determining dividend policy. Dividends are very meaningful for shareholders to increase their wealth, on the other hand, dividends are a source of funds that can be used for investments that produce high returns. In addition, dividends are a positive signal for investors, if the company regularly distributes dividends, this results in a high share price of the company. The manager needs to consider a dividend strategy that can benefit the company's continuation in the future as well as stockholder confidence.      The sample of this research consists of the manufacturing industry on the Indonesia Stock Exchange and starting from 2016-2019 with a total of 32 samples. This research aims to prove the factors of free cash flow (FCF), debt and dividends and their effect on dividend policy by using multiple regression models. The result of the research illustrates that there is a negative effect between free cash flow and dividend policy and this hypothesis is rejected because it is contrary to the hypothesis made. Meanwhile, dividend policy is influenced by debt policy and the result is significantly negative, and company growth has a negative and significant impact on debt policy.